Expression and localization of fibroblast growth factor (FGF) family in buffalo ovarian follicle during different stages of development and modulatory role of FGF2 on steroidogenesis and survival of cultured buffalo granulosa cells. (October 2016) - Mishra, S.R.; Thakur, N.; Somal, A.; Parmar, M.S.; Reshma, R.; Rajesh, G.; Yadav, V.P.; Bharti, M.K.; Bharati, Jaya; Paul, A.; Chouhan, V.S.; Sharma, G.T.; et al.
Abstract: The present study investigated the expression and localization of FGF and its functional receptors in the follicle of buffalo and the treatment of FGF2 on mRNA expression of CYP19A1 (aromatase), PCNA, and BAX (BCL-2 associated X protein) in cultured buffalo granulosa cells (GCs). Follicles were classified into four groups based on size and E2 level in follicular fluid (FF): F1, 4–6 mm diameter, E2  < 0.5 ng/ml of FF; F2, 7–9 mm, E2  = 0.5–5 ng/ml; F3, 10–13 mm, E2  = 5–40 ng/ml; F4, > 14 mm, E2  > 180 ng/ml. The qPCR studies revealed that the mRNA expression of FGF1, FGF2 and FGF7 were maximum (P < 0.05) in theca interna (TI) whereas the transcripts of FGFR1, FGFR2, FGFR2IIIB and FGFR2IIIC were up-regulated (P < 0.05) in GCs of F4 follicles. Protein expression of most members were maximum (P < 0.05) in F4 follicles except FGFR3 and FGFR4. All members were localized in GC and TI with a stage specific immunoreactivity. Primary culture of GCs with treatment of FGF2 at different dose-time combinations revealed that the mRNA expression and immunoreactivity of CYP19A1 and PCNA were maximum (P < 0.05) whereas BAX was minimum (P < 0.05) with 200 ng/ml at 72 h of incubation. The findings indicate that FGF family members are expressed in a regulated manner in buffalo ovarian follicles during different stages of development where FGF2 may promote steroidogenesis and GC survival through autocrine and paracrine manner. Highlights: FGF family members are expressed in regulated manner during different stages of follicular development in Bubalus bubalis . FGF2 stimulates granulosa cell steroidogenesis. FGF2 possibly acts as a cytoprotective factor. Thereby it promotes granulosa cell survival.